2017
DOI: 10.1111/eufm.12139
|View full text |Cite
|
Sign up to set email alerts
|

The mixed vs the integrated approach to style investing: Much ado about nothing?

Abstract: We study the difference between the returns to the integrated approach to style investing and those to the mixed approach. Unlike the mixed approach, the integrated approach aggregates factor characteristics at security level. Recent literature finds that the integrated approach dominates the mixed approach. Using statistical tools for robust performance testing, we demystify these findings as a statistical fluke. We do not find any evidence favouring the integrated approach. What we do find is that the integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…However, in the performance comparison between the TD and BU approach, factor exposures alone provided no sufficient answer to the dissent in the literature. Because, even without any exposure adjustments Amenc et al (2018) and Leippold and Rueegg (2018) did not find significant performance differences between both approaches.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…However, in the performance comparison between the TD and BU approach, factor exposures alone provided no sufficient answer to the dissent in the literature. Because, even without any exposure adjustments Amenc et al (2018) and Leippold and Rueegg (2018) did not find significant performance differences between both approaches.…”
mentioning
confidence: 86%
“…Across the recent literature, there has been no consensus on the superiority of one approach against the other. While Bender and Wang (2016), Clarke et al (2016) as well as Fitzgibbons et al (2017) demonstrated that the BU method leads to better performance results, Chow et al (2018), Leippold and Rueegg (2018) and Amenc et al (2018) reassessed the claim and found no such superiority. In an attempt to balance this discussion, Ghayur et al (2018) emphasized the increased efficiency of the BU approach in gaining a higher exposure to the chosen factors.…”
mentioning
confidence: 93%
“…our robust statistical test framework. Hence, the long-only integrated approach does not dominate the traditional long-short mixed portfolio construction as it is shown in Leippold and Rüegg (2018). Consequently, the success of our one-month momentum strategy does not rely on the actual risk premium of the underlying traditional long-short factors, and it is a winning strategy when we are uncertain about whether the underlying factor bears a positive premium.…”
Section: Introductionmentioning
confidence: 91%
“…In our setting, however, the 1/N strategy is not applied to stocks, but to factor score weights. Therefore, the naive diversification strategy in this set-up corresponds to the integrated strategies presented and analysed in Bender and Wang (2016) and Leippold and Rüegg (2018).…”
Section: Naive Diversification and Fama-macbeth Strategymentioning
confidence: 99%
“…Our article speaks to a recent but quickly growing literature on style-integration in equity markets (Brandt et al, 2009;Frazzini et al, 2013;Fischer and Gallmeyer, 2016;Fitzgibbons et al, 2016;Ghysels et al, 2016;Leippold and Rueegg, 2018;DeMiguel et al, 2019), currency markets (Kroencke et al, 2014;Barroso and Santa-Clara, 2015b) and commodity markets (Fuertes et al, 2015). A common denominator to these studies is their focus on one or at most two style-integration approaches.…”
Section: Introductionmentioning
confidence: 93%